2018
DOI: 10.3389/fimmu.2017.01971
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Host–Commensal Interactions in the Respiratory Tract

Abstract: Commensal microbes are currently in the limelight in biomedical research because they play an important role in health and disease. Humans harbor an enormous diversity of commensals in various parts of the body, including the gastrointestinal and respiratory tracts. Advancement in metagenomic and other omic approaches, and development of suitable animal models have provided an unprecedented appreciation into the diversity of commensals, and the intricacies of their intimate communication with the host immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…To define the characteristic upper airway microbiota and its changes during MV, we evaluated the prevalence of each bacteria genera. The analysis over time confirmed the principal role of Streptococcus as commensal bacteria of the respiratory tract microbiota, confirming previous identification of positive association with healthy lungs [38,39] and possible negative association with the development of lung disease [40]. Furthermore, some genera (Actinomyces, Rothia, Granulicatella and Streptococcus) are more represented during intubation than during ventilation.…”
Section: Discussionsupporting
confidence: 82%
“…To define the characteristic upper airway microbiota and its changes during MV, we evaluated the prevalence of each bacteria genera. The analysis over time confirmed the principal role of Streptococcus as commensal bacteria of the respiratory tract microbiota, confirming previous identification of positive association with healthy lungs [38,39] and possible negative association with the development of lung disease [40]. Furthermore, some genera (Actinomyces, Rothia, Granulicatella and Streptococcus) are more represented during intubation than during ventilation.…”
Section: Discussionsupporting
confidence: 82%
“…While it is not surprising that some human populations have adapted to the presence of certain pathogens by becoming more resistant, the population in this case has become less resistant, as if it actually benefits from infection by respiratory viruses. Some immunologists have suggested that such viruses boost the immune response of lung tissue and thereby prevent more serious pulmonary diseases, like tuberculosis, pneumonia, and pneumonic plague [8]. This preventive effect has been shown with other viruses.…”
Section: Perspective Articlementioning
confidence: 99%
“…Therefore, maternal genetics, environment and diet during pregnancy and after birth influence the bacterial colonization in infants (Kim et al 2020). As during colonization, microbes face a challenging and dynamic Table 1 Role of the human gut microbes in human health Benefits to human health Enterotypes involved environment of the human gut, they have to establish a commensal interaction to stabilize as a gut microbiome (Shekhar et al 2017). Various studies have successfully enlisted microbial genetic and physiological traits to pass through these selective channels to ensure itself as a member of the human gut microbiome (Fig.…”
Section: Gut Microbiomementioning
confidence: 99%
“…As during colonization, microbes face a challenging and dynamic environment of the human gut, they have to establish a commensal interaction to stabilize as a gut microbiome (Shekhar et al . 2017). Various studies have successfully enlisted microbial genetic and physiological traits to pass through these selective channels to ensure itself as a member of the human gut microbiome (Fig.…”
Section: Gut Microbiomementioning
confidence: 99%